2020
DOI: 10.1097/md.0000000000019161
|View full text |Cite
|
Sign up to set email alerts
|

Association between personality traits and suicidality by age groups in a nationally representative Korean sample

Abstract: Suicide is a leading health issue, which substantially contributes to the causes of death worldwide. Personality traits are some of the major risk factors for suicidality. We sought to identify the relationships between personality traits and suicidality by age group.The Big-Five Inventory-10 traits were measured in community-dwelling individuals in a nationally representative sample in the Republic of Korea. Because personality traits are long-standing patterns throughout one's lifetime, suicidality was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
4
7
0
2
Order By: Relevance
“…An association of neuroticism with increased suicidal behavior risk has already been described in population-based cohorts [14,28,29] and studies on individuals with personality [30] or affective disorders [31][32][33]; our secondary analyses confirmed these findings in patients with MDD (the largest diagnostic group in our study) and showed similar effects for BD and SCZ, suggesting that neuroticism may represent a transdiagnostic risk factor for SI [34].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An association of neuroticism with increased suicidal behavior risk has already been described in population-based cohorts [14,28,29] and studies on individuals with personality [30] or affective disorders [31][32][33]; our secondary analyses confirmed these findings in patients with MDD (the largest diagnostic group in our study) and showed similar effects for BD and SCZ, suggesting that neuroticism may represent a transdiagnostic risk factor for SI [34].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, high extraversion is associated with higher levels of energy and sociability and more positive affect [12]. Hence, multiple studies have provided compelling evidence that high neuroticism and low extraversion are important risk factors for suicidal behavior [13][14][15]. A substantial amount of the phenotypic variance of these personality traits is explained by common genetic variants: single-nucleotide polymorphism (SNP)-based heritability estimates range from 6 to 15% for neuroticism and 5% to 18% for extraversion [11,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, severe suicide attempters showed significantly higher hopelessness than the general population (Wolfe et al, 2019). In addition, neuroticism is a personality trait that has recently been identified as the most important predictor of suicide risk among youth (Hafferty et al, 2019;Khosravi & Kasaeiyan, 2020;Na et al, 2020). A higher level of neuroticism level causes vulnerability, anxiety, impulsivity, depression, and angry hostility.…”
Section: Figure2 Psychological Risk Factors In Suicidementioning
confidence: 99%
“…In addition, anxiety traits/disorders and impaired self‐control have been closely related to the transition from SI to SA (Nock et al, 2009 ). Other personality traits, such as agreeableness and conscientiousness, have been linked with reduced SI rates, while neuroticism and openness were associated with higher SI, though all these effects were age dependent (Na et al, 2020 ). Individuals with early‐onset SA exhibited higher levels of neuroticism and lower levels of extroversion than nonsuicidal depressed individuals, while those with late‐onset SA outperformed depressed controls on orderliness, a subcomponent of conscientiousness (Szucs, Szanto, Wright, & Dombrovski, 2020 ).…”
Section: Introductionmentioning
confidence: 99%